Theoretical Study of Pentacoordinated Lanthanide Single-Ion Magnets via Ab Initio Electronic Structure Calculation - Yu-Xi Wang; Yu-Fei Wang; Bing Yin (Magnetochemistry)
A theoretical study, based on ab initio electronic structure calculation, is performed in a group of 16 pentacoordinate Dy-SIMs. Theoretical results provide a reasonable explanation of the observed SMM performance based on a concise criterion, i.e., the co-existence of long τQTM and high Ueff. To have the desired electronic structure favoring good SMM performance, the contribution from the equatorial coordinating atoms might be even more important than that from the axial coordinating atoms. Widening the axial ∠O–Dy–O might be a probable way to improve the SMM performance of pentacoordinated Dy-SIMs. Starting from existing systems, a rigid-scan type exploration indicates the possibility of Ueff higher than 1600 K.